Effect of Growth Regulators on Mustard (Brassica Juncea (L.) Czern And Coss.) Variety Varuna Under Stress and Non-Stress Conditions of Soil Moisture - Patel, M M; Mehta, H M (Annals of Arid Zone, 2016)
Under non-stress conditions of soil moisture, application of succinic acid and cycocel gave significantly higher yield of mustard. Between growth regulators, concentrations and frequency of spray. the differences were not apparent. Single spray application of 500 ppm succinic acid at 43 DAS along with three irrigations gave 14.10% and with single irrigation gave 11.45% higher yield over no application. The incremental cost: benefit ratios for growth regulators were encouraging. It was 1 : 6.69 for succinic acid and 1 : 3.53 for cycocel under stress conditions of soil moisture.